ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN KONSUMEN ONLINE DI E-COMMERCE SHOPEE - Tarigan, Rikki Gunawan; Devin, Devin; Malau, Yois Nelsari; Ginting, Wenny Anggresia (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to examine and analyze the factors influencing online consumer purchasing decisions on the Shopee e-commerce platform, where the independent variables used are Price, Product Quality, Product Reviews, Product Ratings, and Shopping Experience, with Purchasing Decision serving as the dependent variable. The research method used is a quantitative approach. The data collection technique employed in this study is a questionnaire, which was distributed via an online Google Form, yielding 100 respondent samples selected randomly using the Simple Random Sampling technique. The simultaneous results of the F-test indicate that the variables Price, Product Quality, Product Reviews, Product Ratings, and Shopping Experience collectively have a positive influence on Purchase Decision. Meanwhile, the partial results of the study using a t-test indicate that the variables of Price, Product Reviews, Product Ratings, and Shopping Experience do not have a partial or significant effect on the Purchase Decision, whereas Product Quality has a partial and significant effect on the Purchase Decision